2014
DOI: 10.3109/21681805.2014.936495
|View full text |Cite
|
Sign up to set email alerts
|

Lower urinary tract symptoms are associated with low levels of serum serotonin, high levels of adiponectin and fasting glucose, and benign prostatic enlargement

Abstract: The study did not show an association between LUTS or urinary incontinence and the major components of the MetS. However, serum serotonin showed an independent negative correlation with LUTS and with urinary incontinence while fasting serum glucose and serum adiponectin showed a positive correlation with LUTS. The data confirm the general knowledge that BPE may be one of the causative factors of LUTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
1
8
1
1
Order By: Relevance
“…Overall, it may suggest that pharmacological modulation of peripheral 5-HT can be used to efficiently increase prostatic 5-HT and, in this way, inhibit prostatic growth. These findings are also consistent with a preceding study in a large cohort of human males, that established that LUTS were associated with benign prostate increase and plasmatic 5-HT decrease 10 . Furthermore, Sayed et al showed that dapoxetine, a selective serotonin reuptake inhibitor, may inhibit prostatic growth significantly 23 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Overall, it may suggest that pharmacological modulation of peripheral 5-HT can be used to efficiently increase prostatic 5-HT and, in this way, inhibit prostatic growth. These findings are also consistent with a preceding study in a large cohort of human males, that established that LUTS were associated with benign prostate increase and plasmatic 5-HT decrease 10 . Furthermore, Sayed et al showed that dapoxetine, a selective serotonin reuptake inhibitor, may inhibit prostatic growth significantly 23 .…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, in the prostate, 5-HT is one of the most abundant neuroendocrine factors present in neuroendocrine cells (NEC) 9 . It has been reported, in a large humans study, that LUTS were associated with BPH and, at the same time, with a decrease in plasmatic 5-HT concentration 10 . Several reports have also demonstrated that NEC and 5-HT are significantly decreased in BPH when compared to normal prostate 11 13 .…”
Section: Introductionmentioning
confidence: 84%
“…Also 5-HT was shown to be significantly depleted in BPH tissue 19 . Furthermore, a recent study in a large cohort of Scandinavian men revealed that LUTS are associated with benign prostate enlargement and to decreased plasmatic 5-HT concentration 21 . These findings suggest a potential link between prostatic 5-HT depletion and BPH etiology; however, the function of 5-HT in regulation of benign prostate growth has never been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In RCTs, the effect of MetS components on LUTS is unclear because taking a random sample of men and women in the community does mean disorders of the uropoietic system will be present in the sample. 13,42,46 Furthermore, all RCTs are hypothetically designed for sample following a power calculation with 95% CI ( p = 0.05). Even if results are significant, there is a 5% chance they are due to chance.…”
Section: Discussionmentioning
confidence: 99%